Answer:
option C
Step-by-step explanation:
![\frac{\frac{2x-1}{x+2}}{\frac{7}{x^{2}-12}}=\frac{2x-1}{x+2}*\frac{x^{2}-12}{7}\\\\\\=\frac{(2x-1)(x^{2}-12)}{7(x+2)}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cfrac%7B2x-1%7D%7Bx%2B2%7D%7D%7B%5Cfrac%7B7%7D%7Bx%5E%7B2%7D-12%7D%7D%3D%5Cfrac%7B2x-1%7D%7Bx%2B2%7D%2A%5Cfrac%7Bx%5E%7B2%7D-12%7D%7B7%7D%5C%5C%5C%5C%5C%5C%3D%5Cfrac%7B%282x-1%29%28x%5E%7B2%7D-12%29%7D%7B7%28x%2B2%29%7D)
24 x O = 72
You’re looking for an equation where 24 is multiplied by a number to equal 72, so put 72 on one side of the question and multiply 24 by a variable on the other.
Answer:
a) linear
Step-by-step explanation:
Linear keeps a steady pace throughout the function. in the graph, the function is decreasing by 0.5
Before the new kids the ratio of girls to boys is 15:12 because there are 15 girls and 12 boys now you can simplify by dividing 15 by 3 and 12 by 3 to get 5:4 as your simplified ratio. As far as after the new kids. Since there is 1 new girl you do 15+1 to get 16 and there are 3 new boys so you do 12+3 to get 15 now 16:15 is already in simplest form so your answer is:
Before: 15:12 simplified as 5:4
After 16:15
Step-by-step explanation:
6b < 42 or 4b + 12 > 8
6b < 42
= 6b/6 < 42/6
= b < 7
4b + 12 > 8
=4b - 12 + 12 < -12+8
= 4b > - 12 + 8
= 4b > -4
= 4b/4 = -4/4
b > -1
so
7 > b > -1